Designing and managing co-innovation: the case of Loccioni and Pfizer. Issue 4 (16th August 2019) - Ombrosi, Noemi; Casprini, Elena; Piccaluga, Andrea
Abstract : Purpose: Knowing the factors influencing the success of collaborative innovation is particularly relevant for both academics and practitioners. Nonetheless, many studies have regarded the megatrends influencing innovation imperatives, the development of co-innovation strategies, the selection of partners and the involvement of user communities, but not so much the understanding of how the co-innovation process is concretely designed and managed. Adding to extant research, the purpose of this paper is to explore how companies collaborate in co-innovation processes. Design/methodology/approach: A longitudinal, single case study has been conducted on the co-innovation process between Loccioni, an Italian medium-sized, high tech family firm, and Pfizer, one of the largest companies operating in the pharmaceutical sector. Findings: From the case study analysis, three main results have emerged. First, the role of medium-sized companies in leading the co-innovation process as both the initiator and orchestrator. Second, the interplay between the local and the global dimension of co-innovation and the importance of (un)formal roles in innovation. Third, the "double funnel" of co-innovation, linking both the technological and the relational dimensions. Specifically, the case highlights the relevance of the relational – beyond the technological – aspects of co-innovation, providing a relational model that links the geographical dimensions (local/distant) and the role of specific individuals. Originality/value: The paper presents an example of how a medium-sized firm has implemented its co-innovation process, shedding new light on possible barriers and success factors that other smaller or similar companies may follow when dealing with large multinationals.